La resistencia aeróbica en el rendimiento físico de los estudiantes de categoría juvenil que practican futbol en la Unidad Educativa Abdón Calderón Muñoz parroquia Barreiro, cantón Babahoyo, provincia los Ríos - Obando Palma, Enrique Geovanny (2016)
The thesis entitled "Aerobic endurance in physical performance of students in junior category in the educational unit" Abdon Calderon Muñoz "Parish Barreiro, Canton Babahoyo province Rivers" addresses an interesting subject, because in the first instance reveals, by initial diagnosis obtained the level of preparation of teachers of football this educational unit, to address the educational direction of the training process aimed at developing aerobic endurance of students and consequently enhance the performance of these. To obtain the expected results were applied scientific methods of theoretical and empirical level of scientific research, as well as mathematical and statistical methods, with which it was possible to process the data, enabling the analysis of the results developed. The application of the tutorial derived from the research activity deployed can specify in all educational institutions that have football as a specialty responsible for contributing to the process of comprehensive development of the younger generation.